Analisis Anemia Pada Remaja Wanita - Indah Nur Aini; Nabila Meilani Nur Azzahra; Yogi Khoirunnisa Sabila; Nur Indah Ramadhani; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Organization (WHO) in world health statisticsin 2021 shows that the prevalence of anemia in women of reproductive age (15-49) in the world in 2019 is around 29.9%. The results of the 2018 Basic Health Research report by Balitbangkes, in Indonesia the prevalence of anemia in adolescent girls is around 27.2% in the 15-24 year age group. The cause of anemia is generally due to lack of knowledge about anemia, iron deficiency, folic acid, vitamin B12 and Vitamin A. The purpose of this study was to determine anemia in adolescent girls in the Ciputat Region, South Tangerang.This research is a qualitative research. The sample in this study were 7 young womens. Data was collected using triangulation test, processed by data reduction method and presented in the form of narrative text.Most of the young women do not understand anemia so well, so they do not do prevention of anemia such as taking Blood Supplement Tablets (TTD), as a result, young women feel the effects such as dizziness and light-headedness. Poor eating and sleeping patterns and heavy menstruation are the causes of anemia in adolescent girls. Young women still do not understand clearly about anemia, so that anemia suffered by young women is caused by poor eating and sleeping patterns and heavy menstrual expenditure. Teenage girls often experience dizziness and light-headedness due to the anemia they suffer. Adolescent girls have never done prevention of anemia and rarely consume Blood Add Tablets (TTD).It is expected that young women can increase knowledge about anemia.